The variation of soil physical properties in fertile well-drained soils under banana - Leummens, H.J.L. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2021)
90 pág, 16 ilus, 10 tab, 42 ref. También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 115